2015
DOI: 10.1039/c5sc01562f
|View full text |Cite
|
Sign up to set email alerts
|

HOCl can appear in the mitochondria of macrophages during bacterial infection as revealed by a sensitive mitochondrial-targeting fluorescent probe

Abstract: HOCl can appear in the mitochondria of macrophages during bacterial infection as revealed by a new sensitive mitochondrial-targeting fluorescent probe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(89 citation statements)
references
References 37 publications
(34 reference statements)
1
82
0
6
Order By: Relevance
“…[70] Reaction with H 2 O 2 resulted in the ring of the rhodol dye opening with formation of afluorescent product 16' ',thereby resulting in at urn-on response.T he co-localization of MitoPY1 with MitoTracker Red indicated that MitoPY1 specifically localized in the mitochondria of av ariety of mammalian cell types,i ncluding HeLa ( Figure 5), HEK293, Cos-7, and CHO.K1. [74] Upon reaction, ring opening of the spiro-rhodamine triggered substantial and sensitive fluorescence enhancement, which was used to monitor HClO formation within macrophage cells during bacterial infection. [70] As imilar concept was later adopted by Kim and coworkers to develop am itochondria-targetable ratiometric two-photon probe (SHP-Mito (17), Scheme 4) to measure H 2 O 2 .…”
Section: Mitafps For Ros/rns and Redox Balancementioning
confidence: 99%
See 1 more Smart Citation
“…[70] Reaction with H 2 O 2 resulted in the ring of the rhodol dye opening with formation of afluorescent product 16' ',thereby resulting in at urn-on response.T he co-localization of MitoPY1 with MitoTracker Red indicated that MitoPY1 specifically localized in the mitochondria of av ariety of mammalian cell types,i ncluding HeLa ( Figure 5), HEK293, Cos-7, and CHO.K1. [74] Upon reaction, ring opening of the spiro-rhodamine triggered substantial and sensitive fluorescence enhancement, which was used to monitor HClO formation within macrophage cells during bacterial infection. [70] As imilar concept was later adopted by Kim and coworkers to develop am itochondria-targetable ratiometric two-photon probe (SHP-Mito (17), Scheme 4) to measure H 2 O 2 .…”
Section: Mitafps For Ros/rns and Redox Balancementioning
confidence: 99%
“…Confocal imaging experiments confirmed that the probe enabled the assessment of both endogenous production and changes in H 2 O 2 levels within the mitochondria of live cells. [74] Several more examples that incorporate charged pyridine groups or TPP as the mitochondria-targeting motif have also been reported as HClO probes (e.g. [71] This probe utilizes 6-(benzo[d]thiazol-20-yl)-2-(N,Ndimethylamino)naphthalene as at wo-photon fluorophore, ab oronate group as the H 2 O 2 -reactive site and fluorophore masking moiety,a nd with TPP as the mitochondria vector.…”
Section: Mitafps For Ros/rns and Redox Balancementioning
confidence: 99%
“…The Ma group et al developed am itochondria targeting fluorescent probe to detect for HOCl (Scheme 65). [74] This small molecule-based probe shows important properties such as mitochondrial-targeting ability (positivelyc harged) species, af ast response and highs electivity and sensitivity.I np articular,t he limit of detection was found to be 9nm.T his molecular recognition mode showing af luorescent "turn-on" response is due to the spiroring-opening of the rhodamine thiolactoneo ft he probe.T od emonstrate the ability of mitochondrial-targeting, confocal microscopy imaging was exploited. Thep robe was incubated to RAW2 64.7 macrophage cells;t he confocal imaging data shows that the probe can be used to detect endogenous HOCl.…”
Section: Scheme59mentioning
confidence: 99%
“…The Ma group et al. developed a mitochondria targeting fluorescent probe to detect for HOCl (Scheme ) . This small molecule‐based probe shows important properties such as mitochondrial‐targeting ability (positively charged) species, a fast response and high selectivity and sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Toward this end, there have a number of fluorescent probes for HOCl been developed and used in living systems. But most of them are based on changes of the intensity, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] which are limited to the quantification of HOCl due to the fluorescence intensity may be influenced by some external factors such as the concentration of probe, test temperature and instrument performance. Some small molecular based ratiometric HOCl probes have been constructed successfully.…”
Section: Introductionmentioning
confidence: 99%